Effect of glutathione supplementation in extender on quality and fertility of cryopreserved buffalo semen - SINGH, A K; WADHWA, B S; KUMAR, A; HONPARKHE, M; SINGH, N; SINGH, P (The Indian Journal of Animal Sciences, 2024)
Glutathione is integral component of cell membrane that has the ability to protect the structural and functional integrity of buffalo spermatozoa during freeze-thawing. The present study was carried out to assess the effect of different concentrations of glutathione on freezability and in vivo fertility of buffalo sperm. Twenty four semen ejaculates from four healthy breeding Murrah buffalo bulls were collected using artificial vagina. Qualified ejaculates (>70% motility and >3 mass activity) were diluted with Tris-citric acid extender containing 0.0 (control), 0.5, 1.0, 1.5 and 2.0 mM/ml glutathione at 37oC and cryopreserved following established protocol. The frozen-thawed semen was evaluated for CASA-based sperm kinematic traits, viability, plasma membrane integrity, acrosome integrity, mitochondrial membrane potential and lipid peroxidation (LPO). The sperm total and progressive motility, viability, plasma membrane integrity and mitochondrial membrane potential were higher in the extender containing 0.5 mM/ml as compared to other concentrations of glutathione and control. No difference in the percentage of intact acrosomes was observed in all experimental extenders containing glutathione and control. The malondialdehyde (MDA) production was lower in extender supplemented with glutathione (0.5 mM/ml and 1.0 mM/ml) than in other treatments and control. A total of 60 inseminations were performed with the best evolved extender having glutathione (0.5 mM/ml) and control (0.0 mM/ml, 30 inseminations each). In vivo fertility rates were non-significantly higher with extender containing glutathione (0.5 mM/ml; 46.7%) than with control (33.3%). In conclusion, supplementation of 0.5 mM/ml glutathione in extender improved the quality and fertility of cryopreserved buffalo semen.